Development of novel primers for species identification and population genetic studies of ancient swamp buffalo remains - Boonleang, Pee; Sangsom, Jirakit; Krajaejun, Pipad; Wattanapituksakul, Athiwat; Surat, Wunrada (Agriculture and Natural Resources, 2025)
Importance of the work: Ancient domestic buffalo remains have been discovered in China and Thailand, suggesting that they were domesticated in these countries thousands of years ago. However, no genetic information of ancient buffaloes has been used to confirm this. Objectives: To design primers for amplifying ancient DNA of swamp buffaloes. Materials and Methods: The 49 complete D-loop sequences of three buffalo species (river, swamp, and wild water) from Asia and other regions were used to analyze polymorphism distributions for identifying suitable regions for species identification and studying the population genetics of the ancient specimens. Then, primers were designed and the sequences within each primer pair were used for phylogenetic analyses. Modern and ancient specimens were used to test the performance of the primers. Results: The nucleotide polymorphisms of swamp buffaloes, mostly located between the 100th–500th positions of the complete D-loop, were used to design primers within this region. Then, the phylogenetic tree of the complete D-loop and those of sequences within each primer set were compared. Topologies and bootstrap values of the tree from Primer I had the most similarity to that of the complete D-loop tree. In addition, nested polymerase chain reaction (PCR) with Primer I and Primer II could successfully amplify the ancient DNA sample. Main findings: This was the first report of the successful amplification of ancient DNA from swamp buffalo. Nested PCR with the new primers could be used to amplify ancient DNA samples and their sequences could be further used for species identification and studying the origin of swamp buffaloes.